Local estimates of solutions of the stationary two-dimensional first boundary-value problem of magnetohydrodynamics - Britov, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For solutions of a two-dimensional first boundary-value problem of magnetohydrodynamics, we obtaina priori asymptotic (for high Hartmann numbers) estimates of components of the velocity of a liquid and the stream function in the interior of the flow in spaces of continuous functions.